2021
DOI: 10.1080/14737159.2021.1882305
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between positivity for COVID-19 RT-PCR and symptoms, clinical findings, and mortality in Turkey

Abstract: Introduction : This study aimed to assess the correlation between nucleic acid amplification test (real-time reverse transcription-polymerase chain reaction, RT-PCR) positivity of patients presenting with suspected COVID-19 and pneumonic infiltration consistent with COVID-19-specific pneumonia diagnosis on thoracic computed tomography (CT), with symptoms, laboratory findings, and clinical progression. Methods : The study included 286 patients (female:male 131:155; mean age, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A quarter of the patients were health care workers. These demographic findings are comparable to the experiences shared by other investigators [ 11 , 12 ]. This is the first published study describing advanced and organized treatment of hospitalized COVID-19 patients in this country.…”
Section: Discussionsupporting
confidence: 90%
“…A quarter of the patients were health care workers. These demographic findings are comparable to the experiences shared by other investigators [ 11 , 12 ]. This is the first published study describing advanced and organized treatment of hospitalized COVID-19 patients in this country.…”
Section: Discussionsupporting
confidence: 90%
“…In the first study evaluating mortality from the Central Asia and Eurasia regions, Gaipov et al [5] reported that positive RT-PCR cases had a twofold higher risk of mortality than negative counterparts. In contrast, in a study from Turkey, Ozcan et al [6] reported that among patients with suspected COVID-19 and positive CT findings, mortality rates were not statistically different between RT-PCR positive and RT-PCR negative patients. Moreover, the literature suggests that chest CT severity is correlated with disease severity and mortality in COVID-19 [7][8][9].…”
Section: Discussionmentioning
confidence: 84%
“…Patients with viral pneumonia may have a negative RT-PCR test [2,3], and conversely, patients with a COVID-19 infection may have a normal chest CT [4]. Moreover, previous literature reports a wide variety of results regarding the association between RT-PCR and chest CT results with hospitalization and mortality [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors had already reported similar results. Ozcan et al in Turkey 28 found a highly significant correlation between the presence of anosmia and/or aguesia in a patient and RT-PCR positivity. Anosmia/aguesia, fever, and myalgia were the strongest independent predictors of positive RT-PCR tests for COVID-19 in the study by Fan-Yun et al among healthcare workers in the United States.…”
Section: Discussionmentioning
confidence: 96%